2009
DOI: 10.3109/17435390903337693
|View full text |Cite
|
Sign up to set email alerts
|

Copper nanoparticles exert size and concentration dependent toxicity on somatosensory neurons of rat

Abstract: Metal nanoparticles, due to their unique properties and important applications in optical, magnetic, thermal, electrical, sensor devices and cosmetics, are beginning to be widely manufactured and used. This new and rapidly growing field of technology warrants a thorough examination of the material's bio-compatibility and safety. Ultra-small particles may adversely affect living cells and organisms since they can easily penetrate the body through skin contact, inhalation and ingestion. Retrograde transport of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(126 citation statements)
references
References 43 publications
6
119
0
1
Order By: Relevance
“…[8][9][10][11][12][13][14] Recently, a new type of nano-Cu IUD was invented by However, numerous studies have unequivocally indicated that exposure to Cu NPs can result in adverse effects in vivo and in vitro. [16][17][18][19][20] For instance, a previous study demonstrated that the exposure of mice to Cu NPs resulted in severe kidney, liver, and spleen impairment. 16 Another study further revealed that the nephrotoxicity of Cu NPs was highly correlated with significant alterations in the expression of many genes, such as those involved in oxidative phosphorylation, the cell cycle, the mitogen-activated protein kinase signaling pathway, and glutathione metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Recently, a new type of nano-Cu IUD was invented by However, numerous studies have unequivocally indicated that exposure to Cu NPs can result in adverse effects in vivo and in vitro. [16][17][18][19][20] For instance, a previous study demonstrated that the exposure of mice to Cu NPs resulted in severe kidney, liver, and spleen impairment. 16 Another study further revealed that the nephrotoxicity of Cu NPs was highly correlated with significant alterations in the expression of many genes, such as those involved in oxidative phosphorylation, the cell cycle, the mitogen-activated protein kinase signaling pathway, and glutathione metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Currently nanotoxicology studies often employ LDH as a simple cytotoxicity marker [10,30,31]. Elevated LDH levels have been detected in in vitro cell studies of NPs [32], but in the literature conclusions about mechanisms and impacts are mixed.…”
Section: Discussion (A) Engineered Nanoparticle Agglomeration In Condmentioning
confidence: 99%
“…37 Size-dependent neurotoxicity of copper nanomaterials (40-80 nm) was demonstrated in murine somatosensory neurons, with smaller particles being more toxic than larger ones. 38 The cytotoxicity of nanosized and microsized CuO materials was studied in a human alveolar cell line. 39 The 42 nm particles were significantly more toxic to the mitochondria and DNA than were the 3 µm particles.…”
Section: Discussionmentioning
confidence: 99%